Shift in diet composition of Indian mackerel Rastrelliger kanagurta – an analysis in relation to climate change - Supraba, V.; Dineshbabu, A. P.; Thomas, Sujitha; Rohit, Prathibha; Rajesh, K. M.; Zacharia, P. U. (Indian Journal of Fisheries, 2016)
The feeding regime of organisms depend on the plankton community structure which is being studied worldwide to assess the changes in marine ecosystem structure due to climate change or anthropogenic activities. An attempt is made here to study the seasonal and long term variation in feed composition of Indian mackerel over a period of 40 years and its relationship with sea surface temperature to elucidate structural changes in food composition if any over period of time and its relationship to the primary and secondary productivity in eastern Arabian Sea marine ecosystem. The diet study during 2011-2014 reported the domination of phytoplankton consisting of Coscinodiscus sp. consistently and the presence of macroplankton and fish larvae whereas the diet during 1960-1961 showed the dominance of zooplankton and copepods. It could be assumed that increase in sea surface temperature which resulted in dominance of phytoplankton community as reported elsewhere in the world is also observed in eastern Arabian Sea which is reflected in the diet regime of Indian mackerel. The results also indicate its facultative feeding behaviour by compensating the low value phytoplankton with high value macroplankton and hence can be considered as a resilient species with regard to climate change.